A Note on CCMV Portfolio Optimization Model with Short Selling and Risk-neutral Interest Rate - Tahereh Khodamoradi; Maziar Salahi; Ali Reza Najafi (Statistics, Optimization & Information Computing, 2020)
In this paper, first we present some drawbacks of the cardinality constrained mean-variance (CCMV) portfolio optimization with short selling and risk-neutral interest rate when the lower and upper bounds of the assets contributions are -1/K and 1/K(K denotes the number of assets in portfolio). Then, we present an improved variant using absolute returns instead of the returns to include short selling in the model. Finally, some numerical results are provided using the data set of the S&P 500 index, Information Technology, and the MIBTEL index in terms of returns and Sharpe ratios to compare the proposed models with those in the literature.